Case Report: Complete response to four cycles of camrelizumab in a PD-L1 negative patient with advanced oral squamous cancer - He, Jianqiao; Yu, Guoning; Ma, Yi; Shi, Xiaoqiong; Gao, Yingna; Zheng, Hongliang; Zhu, Minhui; Zhang, Caiyun (Frontiers in Immunology, 2025)
Immunotherapy has brought better survival benefits in the treatment of recurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC). However, owing to the lack of relevant biomarkers that could predict the efficacy of this treatment, it often has to be maintained. Here we report on a patient with stage IVA squamous cell carcinoma of the tongue who developed an unresectable lesion in the neck after surgery and radical chemoradiotherapy. After four cycles of intermittent immunotherapy with camrelizumab, complete response (CR) was achieved. Next-generation sequencing showed that the TP53/FANCA/FAT1 gene mutations and negative PD-L1 expression were involved. The patient has been followed up for 4 years without R/M. This situation has not been reported previously, suggesting that some patients can benefit from short-term immunotherapy and even achieve CR; moreover, there may be more molecular markers to be discovered that can predict the efficacy of immunotherapy. We can conduct in-depth research on relevant molecular markers, formulate personalized immunotherapy strategies and plans, and facilitate the development of new precision treatment strategies for HNSCC.